Use of the [Copper(II)/MAA-nylon] Complex for the Adsorption of Residual Acid Dyes - Chahira Makhlouf; Mohamed Hassen V Baouab; Sadok Roudesli (Adsorption Science & Technology)
Nylon fibres were converted into a strong ion-exchange polymer by grafting with methacrylic acid (MAA). The modified nylon fibres were monitored for their ability to remove copper(II) ions and dyes from aqueous solutions. Evidence for the grafting of MAA onto nylon was provided by weight uptake experiments and atomic force microscopy (AFM). The exchange capacity of MAA–nylon was evaluated by potentiometric titration of the grafted acidic groups. Due to complexation, the acidic grafted groups immobilize Cu(II) ions from Clark–Lub's buffered solution at a pH value of 8. The formation of a 1:1 complex was demonstrated by the values of the adsorption limits. The binary [Cu(II)/MAA–nylon] system was then tested for the adsorption of two Acid dyes, i.e. Acid Blue 25 (AB 25) and Calmagite (Calma), as ligands in the metal-coordinating process. The adsorption of Cu(II) onto MAA–nylon and of the dyes onto Cu(II)/MAA–nylon was followed spectrometrically. The observed stoichiometries of the ternary [dye/Cu(II)/MAA–nylon] complex formed were [ ] for AB 25 and [ ] for Calma at 20°C. Theoretical modelling of the adsorption process was performed employing the Langmuir, Freundlich and Jossen equations. Thermodynamic parameters such as the free energy change (ΔG 0 ), the enthalpy change (ΔH 0 ) and the entropy change (ΔS 0 ) for adsorption were also investigated. The adsorption process is exothermic, which leads to a reduction in the extent of dye adsorption with increasing temperature.